إستخلاص السليلوز من بقايا شجرة نخيل التمر Phoenix dactylifera. L ودراسة خصائصه - فطحيزة التجاني, شعيب (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2020)
الملخص: الهدف من هذه العمل هو دراسة وتثمين مخلفات النخيل وذلك باعتبارها مصدر للمواد الطبيعة المتجددة، في هذا العمل قمنا باستخلاص ألياف السليلوز من خمسة أجزاء مختلفة من مخلفات النخيل باستعمال المعالجة القاعدية ثم التبيض بالـ (NaClO2) كما تم تحديد كمية المواد الرئيسية في المخلفات (اللجنين، الهميسليلوز، المواد المستخلصة)، حيث تراوح مردود السليلوز ما بين %(41.46-37.76)، كما تم فحص مخلفات النخيل وألياف السليلوز المستخلص بعدة تقنيات، طيف الأشعة تحت الحمراء لتحويل فورييه (FT-IR) الذي أظهر اختفاء الوظائف الكيميائية المعبرة عن المواد الغير سليلوزية في الالياف المستخلصة، طيف الاشعة الصينية (XRD) الذي أوضح الزيادة في نسبة التبلور % (Cr)، أما البنية المورفولوجيا للألياف السليلوز تم فحصها بـالمجهر الالكتروني الماسح (SEM) حيث أظهرت الصور سلامة الألياف ونقاوتها، كما تم من خلال تقنية التحليل الكيميائي الطيفي (EDS) التأكيد على أن العينات عبارة عن كربوهيدرات لاحتوائها على الكربون والأكسجين فقط، بينما في الجزء الثاني من الدراسة العملية تم تصنيع مواد أخرى انطلاقا من المخلفات وألياف السليلوز المشخصة سابقا، حيث تم تحضير خلات السليلوز انطلاقا من السليلوز المستخلص من الغمد، كما تم تأكيد حدوث الاستبدال باستعمال طيف (FT-IR)، كتطبيق ثاني وبخطوة واحدة فقط تم تصنيع (Carbon Nano Structures) من رماد ألياف السليلوز واستعمالها كمستشعر لتحديد جودة البترول الخام، وقد أكدة نتائج طيف الأشعة تحت الحمراء (FT-IR) وطيف الاشعة الصينية (XRD) على أنها هياكل نانو كربونية كما أظهرت الدراسة باستخدام التحليل الطيفي للأشعة المرئية وفوق البنفسجية (UV-Vis) لـ(CNS) أن لها قدرة على استشعار المركبات البترولية وتم تحديد الطول الموجي (350nm) والتركيز (0.4ml/l) كأفضل شروط لتحديد جودة البترول. Résumé : فرنسية أو انجلزية This study aims at charachterising and evaluationg paml remains used as a source of a natural renewable material. In this research, micro-cellulose was extracted from five parts of palm remains using Alkali treatment and Bleaching. The percentage principle materials of the remains were identified. Cellulose microfibers yield was foun to be %(41.46-37.76).Palm remains and its Cellulose microfibers were investigated through several techniques, The Fourier-transform infrared spectroscopy indicates the absence of non-cellulose peak. The x-ray spectrum (XRD) showed the increase of crystallization percentage (% Cr). The morphology of the cellulose fibers was examined using a scanning electron microscope (SEM). The images showed the integrity and purity of the fibers, as was done through the technique of chemical analysis spectroscopy (EDS) to confirm The samples are carbohydrates because they contain carbon and oxygen only, while in the second part of the practical study other materials were manufactured from the residues and previously diagnosed cellulose fibers, where the cellulose acetate was prepared from the cellulose extracted from the sheath. the substitution was confirmed using a spectrum (FT-IR), as a second application and ه only one step, Carbon Nano Structures were made from cellulose fiber ash and used as a sensor to determine the quality of crude oil, and the results of the infrared spectrum (FT-IR) and the Chinese ray spectrum (XRD) were confirmed as Nano-structures. Carbon also the study, using UV-Vis spectroscopy of (CNS), showed that it has the ability to sense petroleum compounds, and the wavelength (350nm) and concentration (0.4ml/l) were determined as the best conditions for determining the quality of petroleum.
أطروحة دكتوراه تخصص كيمياء في العلوم الدقيقة
Keywords: اللجنوسليلوز، السليلوز، النخيل، خلات السليلوز، (CNS); lignocellulose, cellulose, palm, cellulose acetate, (CNS).